ANALISIS SISTEM AKUNTANSI PELAKSANAAN APBDes PADA PEMERINTAH DESA KOPANDAKAN I KECAMATAN KOTAMOBAGU SELATAN KOTA KOTAMOBAGU - Gimon, Hadi Prabowo; Tinangon, Jantje J.; Affandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Village income and expenditure budget is one of the things that must be considered to realize good governance in the village. The purpose of this study is to analyze the adequacy of the accounting system implementation of APBDes organized by the Kopandakan I village government and whether it is in accordance with the Minister of Home Affairs No. 113 of 2014 on the management of village finances. The method used in this research is qualitative descriptive that is analyze the adequacy of accounting system implementation of APBDes. The results of the research show that 1) Internal control in terms of producing transaction evidence executed by Kopandakan I village government has been running quite well, 2) Recording of APBDes implementation in Kopandakan I village has been done well 3) Reallocation Report of Implementation of APBDes in Kopandakan Village I has been in accordance with Permendagri Number 113 Year 2014; but village officials have problems in the process of implementing APBDes in this case tax cutting activities but directly in consultation with the tax office.Keywords : Accounting system, implementation, APBDes